Thrombocytopenia Among Pregnant Women in Southwest Ethiopia: Burden, Severity, and Predictors - Haile K; Kebede S; Abera T; Timerga A; Mose A (Journal of Blood Medicine, 2022)
Kassahun Haile,1 Solomon Kebede,1 Temesgen Abera,1 Abebe Timerga,2 Ayenew Mose3 1Department of Medical Laboratory Science, College of Medicine and Health Sciences, Wolkite University, Wolkite, Ethiopia; 2Department of Biomedical Science, College of Medicine and Health Sciences, Wolkite University, Wolkite, Ethiopia; 3Department of Midwifery, College of Medicine and Health Sciences, Wolkite University, Wolkite, EthiopiaCorrespondence: Kassahun Haile, Department of Medical Laboratory Science, College of Medicine and Health Sciences, Wolkite University, P.O. Box: 07, Gubre, Wolkite, Ethiopia, Tel +259-26-07-43-74, Fax +251 11 322 0041, Email kassahaile07@gmail.comBackground: Thrombocytopenia is a worldwide public health problem in pregnant women and is associated with significant maternal–fetal complications and mortality. Determination of burden, severity, and predictors of thrombocytopenia in pregnant women is imperative to develop intervention measures to mitigate their risk and public health impact, which is not well known in Ethiopia, particularly in the selected study area. Thus, this study aimed to determine the burden, severity, and predictors of thrombocytopenia among pregnant women in Wolkite University Specialized Hospital, southwest Ethiopia.Materials and Methods: A cross-sectional study was employed among 422 pregnant women from May to August 2021. A structured questionnaire was used to collect data on socio-demographic, reproductive, and related characteristics. Venous blood samples were collected and platelet counts were determined by Sysmex XP-300 hematology analyzer. A binary logistic regression analysis was performed using SPSS version 22 software to identify independent predictors of thrombocytopenia. The p-value < 0.05 was considered statistically significant.Results: The overall burden of thrombocytopenia among pregnant women was 14.5% (95% CI: 11.4– 17.8). Among them, 77%, 16.4%, and 6.6% had mild, moderate, and severe thrombocytopenia, respectively. Rural residence (AOR: 2.9, 95% CI: 1.5– 5.8), increasing age (AOR: 1.9, 95% CI: 1.04– 3.44), alcohol consumption (AOR: 2.48, 95% CI: 1.3– 4.5), and HIV infection (AOR: 8.5, 95% CI: 1.9– 18.4) were independent predictors of thrombocytopenia among the pregnant women.Conclusion: A high burden of thrombocytopenia (14.5%) was observed among the pregnant women in this study area. Rural residence, increasing age, consumption of alcohol, and HIV infection were identified as independent predictors of thrombocytopenia. The findings of this study should be taken into consideration to conduct appropriate intervention measures on identified predictors and implement routine screening of platelet count, thrombocytopenia diagnosis, and treatments to reduce the burden of morbidity and mortality among pregnant women.Keywords: pregnant women, thrombocytopenia, predictors, Wolkite, Ethiopia